2016
DOI: 10.1002/sdtp.11034
|View full text |Cite
|
Sign up to set email alerts
|

P-131: Studies on Flickering in Low Frequency Driven Fringe-Field Switching (FFS) Liquid Crystal Display

Abstract: Recently, the driving scheme of a fringe-field switching (FFS) liquid crystal display varies for the best of required performance. Although low-frequency driving can effectively give rise to reduce power consumption in portable displays, proper controlling of liquid crystal director in direct current is challenging. Particularly, under different polarity of applied electric fields, the transmittance difference along the location of electrodes becomes significant, hence giving rise to an image flickering issue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Consequently, intensive efforts to reduce the power consumption of this mode have been attempted by using the low‐ f driving when static images are being displayed. However, severe issues regarding image quality arise in the low‐ f driving, including image‐flickering owing to flexoelectric effect . The flexoelectric effect is a coupling between elastic deformation and electric polarization of liquid crystals in which the flexoelectric polarization is spontaneously induced by external electric field at a low f .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, intensive efforts to reduce the power consumption of this mode have been attempted by using the low‐ f driving when static images are being displayed. However, severe issues regarding image quality arise in the low‐ f driving, including image‐flickering owing to flexoelectric effect . The flexoelectric effect is a coupling between elastic deformation and electric polarization of liquid crystals in which the flexoelectric polarization is spontaneously induced by external electric field at a low f .…”
Section: Introductionmentioning
confidence: 99%
“…In order to use a low driving frequency to save energy, the image flickering problem must be solved. [9][10][11][12][13][14] In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD. 15 Ions may cause 2 problems.…”
Section: Introductionmentioning
confidence: 95%
“…However, if the driving frequency is reduced, there is a problem that the brightness of the display may change with time, a phenomenon known as image flickering. In order to use a low driving frequency to save energy, the image flickering problem must be solved . In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD .…”
Section: Introductionmentioning
confidence: 99%
“…However, this low-frequency driving has recently been brought to huge attention owing to a serious image-quality drop, so-called image-flickering. Many reports show flexoelectric effect is one of main reasons of the image-flickering [1][2][3]. Flexoelectric effect is a coupling between geometric distortion of LC director field and the electric polarization [4].…”
Section: Introductionmentioning
confidence: 99%